Antimicrobial properties of lignin-decorated thin multi-walled carbon nanotubes in poly(vinyl alcohol) nanocomposites. (August 2018) - Lee, Eun-Sil; Kim, Young-O; Ha, Yu-Mi; Lim, Daun; Hwang, Jun Yeon; Kim, Jaewoo; Park, Min; Cho, Jae Whan; Jung, Yong Chae
Graphical abstract: Highlights: Lignin-decorated thin multi-walled carbon nanotubeswere prepared to obtain mechanically strong poly(vinyl alcohol) (PVA) nanofibers with high antimicrobial properties. The lignin/t-MWNT/PVA composites showed significantly improved antimicrobial properties compared to lignin/PVA composites. The use of lignin-decorated t-MWNTs in the PVA nanofibers resulted in enhanced mechanical and antimicrobial properties. Lignin-decorated t-MWNT/PVA nanofibers may have a high potential for applications in wound dressings, scaffolds, and antimicrobial textiles. Abstract: Lignin-decorated thin multi-walled carbon nanotubes (t-MWNTs) were prepared to obtain mechanically strong poly(vinyl alcohol) (PVA) nanofibers (NFs) with high antimicrobial properties. The t-MWNTs were well-dispersed in the aqueous lignin solution owing to their good interaction with lignin molecules, resulting in decoration of the lignin molecules on the surface of the t-MWNTs. The lignin-decorated t-MWNT/PVA NF webs were prepared by electrospinning lignin/t-MWNT/PVA solutions containing 1 wt% t-MWNTs. They displayed enhanced mechanical properties in terms of breaking stress and modulus, compared to lignin/PVA nanofibers. Superior antimicrobial activity was also exhibited by the lignin/t-MWNTs/PVA composites compared to lignin/PVA composites. The mechanical properties of the lignin/t-MWNT/PVA NFs could be preserved even after the heat treatment of PVA, which is a necessary process for medical applications such as wound healing on the skin's dermal layer.